2016
DOI: 10.1002/term.2153
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofin vitro-cultivation of human mesenchymal stroma/stem cells derived from bone marrow and umbilical cord

Abstract: Cell-mediated therapy is currently considered as a novel approach for many human diseases. Potential uses range from topic applications with the regeneration of confined tissue areas to systemic applications. Stem cells including mesenchymal stroma/stem cells (MSCs) represent a highly attractive option. Their potential to cure or alleviate human diseases is investigated in a number of clinical trials. A wide variety of methods has been established in the past years for isolation, cultivation and characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 143 publications
1
20
0
3
Order By: Relevance
“…Mesenchymal stem/stromal cells (MSC) represent an important group of adult stem cells with multidifferentiation potential and immunomodulatory properties, making them an important cell type for cell therapy purposes . Currently, more than 400 studies exploring the therapeutic effects of MSC have been registered on the clinical trial database (http://www.clinicaltrials.gov) to treat diseases such as GvHD, organ transplantation, diabetes, multiple sclerosis, and Crohn .…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem/stromal cells (MSC) represent an important group of adult stem cells with multidifferentiation potential and immunomodulatory properties, making them an important cell type for cell therapy purposes . Currently, more than 400 studies exploring the therapeutic effects of MSC have been registered on the clinical trial database (http://www.clinicaltrials.gov) to treat diseases such as GvHD, organ transplantation, diabetes, multiple sclerosis, and Crohn .…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of MSCs derived from the bone marrow is quite simple because it uses the adhesion of these cells to the plastics. Thanks to this, other cells can be separated by rinsing them out several times [8]. MSC can also be obtained from Wharton jelly after thorough cleansing from the blood.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The resulting solution is centrifuged at 300 g for 5 minutes and the pellet can be used for cell culture. The whole procedure must be sterile to avoid the possibility of infection [8,9].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Umbilical cord-derived stem cells (UC-MSCs) are usually cultured at 37°C in a humified 5% CO 2 atmosphere. However it has been reported that the atmospheric concentration of the oxygen can be relatively toxic for the cells and the hypoxic conditions could be beneficial for their growth [5,22]. Since UC-MSCs are plastic-adherent, they are cultured either in flasks or plates and the culture medium is most commonly supplemented with 10% fetal bovine serum (FBS), however the use of 15% FBS has been described as well [23,24].…”
Section: In Vitro Cultivation Of Umbilical Cordderived Cellsmentioning
confidence: 99%